Evaluation of the Adequacy Level of Nutritional Substances (Vitamins) with the Incident of Stunting in Children in the Working Area of the Surabaya City Health Center - Septi Fandinata, Selly; Mas Ulfa, Ninik; Puspa Novita, Rennie; Aryanda Putra, Deddy (International Journal of Science, Technology & Management, 2024)
Stunting is a condition where height growth disorders arise due to malnutrition, so that a child's height does not correspond to his age. The aim of this research is to evaluate the use of vitamins and minerals in stunting cases in several Surabaya Community Health Centers. The results of this research are descriptive with prospective data collection. The number of respondents obtained was 64 stunting child patients who met the inclusion criteria. Based on the results of child demographics according to age, the most stunting child patients were 32 patients aged 48 – 60 months (50%). Based on gender, the results were balanced between women and men. Based on a history of exclusive breastfeeding, the majority had a history of exclusive breastfeeding, 52 patients (81.25%). Based on birth weight, the highest number of patients with a normal weight (>2500) grams was 53 patients (82.82%). Based on disease history, the majority did not have a history of disease, 53 patients (82.82%). The vitamins and minerals used in stunting cases in several Surabaya Community Health Centers are Optima Zinc Syrup, Vitamin and Mineral Powder, Taburia, and Vitamin A Capsules, with the rules and duration of use according to those given. Based on the results of nutritional status assessments at several Surabaya Community Health Centers, it was found that the majority of children were underweight based on Z-Score BW/U, had short status based on Z-Score BH/U, and had good nutritional status based on Z-Score BW/BH. The results of the nutritional status assessment concluded that the majority of children were underweight based on Z-Score BW/U, had short status based on Z-Score BH/U, and had good nutritional status based on Z-Score BW/BH.